Study design of a randomised, placebo-controlled trial of nintedanib in children and adolescents with fibrosing interstitial lung disease. Issue 2 (21st June 2021) - Deterding, Robin; Griese, Matthias; Deutsch, Gail; Warburton, David; DeBoer, Emily M.; Cunningham, Steven; Clement, Annick; Schwerk, Nicolaus; Flaherty, Kevin R.; Brown, Kevin K.; Voss, Florian; Schmid, Ulrike; et al.
Childhood interstitial lung disease (chILD) comprises >200 rare respiratory disorders, with no currently approved therapies and variable prognosis. Nintedanib reduces the rate of forced vital capacity (FVC) decline in adults with progressive fibrosing interstitial lung diseases (ILDs). We present the design of a multicentre, prospective, double-blind, randomised, placebo-controlled clinical trial of nintedanib in patients with fibrosing chILD (1199-0337 or InPedILD;ClinicalTrials.gov : NCT04093024). Male or female children and adolescents aged 6–17 years (≥30; including ≥20 adolescents aged 12–17 years) with clinically significant fibrosing ILD will be randomised 2:1 to receive oral nintedanib or placebo on top of standard of care for 24 weeks (double-blind), followed by variable-duration nintedanib (open-label). Nintedanib dosing will be based on body weight-dependent allometric scaling, with single-step dose reductions permitted to manage adverse events. Eligible patients will have evidence of fibrosis on high-resolution computed tomography (within 12 months of their first screening visit), FVC ≥25% predicted, and clinically significant disease (Fan score of ≥3 or evidence of clinical progression over time). Patients with underlying chronic liver disease, significant pulmonary arterial hypertension, cardiovascular disease, or increased bleeding risk are ineligible. The primary endpoints are pharmacokinetics and the proportion of patients with treatment-emergent adverse events at week 24. Secondary endpoints include change in FVC% predicted from baseline, Pediatric Quality of Life Questionnaire, oxygen saturation, and 6-min walk distance at weeks 24 and 52. Additional efficacy and safety endpoints will be collected to explore long-term effects. We describe the design of #InPedILD, a study of 24 weeks' nintedanib or placebo on top of standard of care, followed by variable-duration open-label nintedanib in children with interstitial lung disease (ClinicalTrials.gov NCT04093024) #PedILD https://bit.ly/3tC1a7P